Influence of the Planting Distance and the Crown Shape on the Fruit Harvest and the Productive Potential of Cherry Trees in a High-Density System - Igor IVANOV; Valerian BALAN; Ananie PEŞTEANU; Sergiu VAMASESCU; Petru BALAN; Vasile SARBAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2018)
Cherry technology is permanently modernized due to new varieties, vegetal rootstocks and new tree management systems. The cherry varieties “Bigarreau Burlat”, “Ferrovia” and “Lapins”, grafted on Gisela 6 (Prunus cerasus × Prunus canescens) rootstock at distances of 5x1.5 m; 5x2.0 m; 5x2.5 m, were studied in the southern area of the Republic of Moldova. The trees were shaped by the Ameliorated natural reduced-volume crown and Slender Spindle Ameliorated form. Cherry trees start to yield in the fourth year after planting; the largest total fruit production from the tree was obtained in the variant with trees planted at a distance of 5x2.5 m and per hectare, when the trees were planted at a distance of 5x1.5 m. In the fourth year of yielding, the production of “Ferrovia” cherry variety, where the trees were shaped by the Ameliorated natural crown with low volume constituted 15368-18155 kg/ha, and at the time the “Slender Spindle Ameliorated” form, constituted 16904 -20074 kg/ha. Although the results are preliminary, it seems that high-density planting systems combined with low-power vegetal rootstocks and improved crowns can give higher yields of cherries in the first 4 years than the traditional improved crown system with low volume.